TRADISI JEJAGA DALAM UPACARA NGUSABA DALEM DI DESA MADENAN KECAMATAN TEJAKULA (PERSPEKTIF TEOLOGI SOSIAL) - Putu Corry Candra Yhani; I Wayan Gata (Jnanasidanta, 2022)
Abstrak: The existance of a tradition in Indonesia, especially the island of Bali itself, contain elements of the Three Basic Fondation of Hinduism or Tri Kerangka Dasar Agama Hindu. One of the cultures in Indonesia, such as the traditions that exist on the island of Bali, especially in the Madenan Village, Tejakula District, which still survives to this day is the Jejaga tradition in the Ngusaba Dalem ceremony. One of them is the Jejaga Tradition, where this tradition aims to celebrate bhuta kala by offering cows and pigs as sacrifices. The uniqueness of this Jejaga tradition is that before the Jejaga tradition is carried out, there is an implementation of brata nyineb kori where people are not allowed to go to temples or Sanggah. The function of ceremonies or rituals contained in the Jejaga tradition which in its implementation also uses facilities in the form of offerings or offerings. Banten or offerings as a means of religious rituals which are sincere offerings or sacrifices to God Almighty have positive meanings for Hindus. The Jejaga tradition also has a social function in society. Living in society is a must for all human beings. Even though in the current era of globalization, which has reached the level of modernity, the sense of togetherness and kinship should not fade. In social life, humans are faced with social phenomena or models of a way of life to achieve common goals. This paper uses a qualitative approach. This is done because one of the workspaces of a qualitative approach is the interpretation of a phenomenon by using thoughts, feelings, perceptions and human mentality to obtain a meaning that is useful for the development of human life